Liderazgo directivo en la gestión escolar desde el enfoque político de la escuela - Contreras Paredes, Blanca Margarita (Pontificia Universidad Católica del Perú. Fondo Editorial, 2009)
This investigation presents the analysis of the relationship between the leadership style of a principal and the participation of teachers and students in school management, from a school and leadership political approach. The study identifies the sources of power from the principal of the school; describes how she develops communications with the different school actors; how she implements her decision-making and how she manages conflicts, among other aspects ofmicro-politics. Similarly, the study details how leadership is influential in the participation levels of teachers and students in school management. Finally, the study contributes in identifying management obstacles, in a context that demands a horizontal approach to the relationship principal-teachers-students, suggesting what to do and what not to do by the leadership.

Esta investigación presenta el análisis de la relación entre el estilo de liderazgo deuna directora y la participación de docentes y alumnos en la gestión escolar, desdeel enfoque político de la escuela y el liderazgo. El estudio identifica fuentes depoder de la dirección, describe la manera en que desarrolla la comunicación conlos diferentes actores; cómo ejerce la toma de decisiones y gestiona los conflictos,entre otros aspectos de la micropolítica. Asimismo, detalla el modo en que el ejerciciode su liderazgo influye en el nivel de participación de docentes y alumnos enla gestión escolar. Finalmente, contribuye a identificar los nudos que entrampanesta gestión, en un contexto donde se demanda horizontalidad en las relacionesdirector-docentes-alumnos, sugiriendo lo que se debe y no se debe hacer desde ladirección.
Keywords: Liderazgo; Participación; Gestión Escolar; Micropolítica; Leadership; Participation; School Management; Micropolitics; https://purl.org/pe-repo/ocde/ford#5.03.00